THE EFFECT OF PONTIC DESIGN TO PERIODONTAL TISSUE - M. Nasrul Nasrul; Ira Tanti; Farisza Gita (Journal of Dentistry Indonesia, 2015)
Pontic is a part of a fixed partial denture that replaces missing teeth. The pontic must fulfill the function of achieveing an esthetic appearance and preventing tissue irritation. The basal surface of the pontic must be well-polished and smooth to preserve the health of the periodontal tissue. Besides that the basal surface of the pontic should be convex to make minimum pressure contact with the alveolar ridge. The inflammation of periodontal tissue is caused by pontic design, which does not fulfill the biologic and hygienic requirements. There are some types of pontic design based on the connection of basal surface pontic with the periodontal tissue; those that contact the oral mucosa and those that do not. The selection of pontic design should consider the space of edentulous area on the vertical and horizontal distance, the form, height, and the location of the residual ridge. Each pontic design has positive and negative factors.